Procyanidin-rich fractions from Parkia biglobosa (Mimosaceae) leaves cause redox-sensitive endothelium-dependent relaxation involving NO and EDHF in porcine coronary artery - Tokoudagba, Jean-Marie; Auger, Cyril; Bréant, Lise; N’Gom, Saliou; Chabert, Philippe; Idris-Khodja, Noureddine; Gbaguidi, A. Fernand; GBENOU, Joachim; MOUDACHIROU, MANSOUROU; Lobstein, Annelise; Schini-Kerth, Valérie B. (My University, 2010)
Aim of the study: Parkia biglobosa leaves are traditionally used as an antihypertensive agent in Benin. The present study assessed the vasorelaxant activity of different Parkia biglobosa leaf extracts using isolated porcine coronary artery rings. Materials and methods: A hydroalcoholic leaf extract was submitted to a multi-step liquid–liquid fractionation with solvents of increasing polarity and the polyphenolic content of the different fractions was analyzed. Vascular reactivity of the different extracts was assessed using porcine coronary artery rings, in the presence or absence of specific pharmacological inhibitors. Results: The hydroalcoholic, ethyl acetate and butanolic extracts contained mainly procyanidins and monomeric flavonoids. Parkia biglobosa leaf crude extract induced a redox-sensitive endotheliumdependent relaxation mediated by both nitric oxide (NO) and endothelium-derived hyperpolarizing factor (EDHF). The fractionation of the butanolic extract generated 6 fractions, two of which induced stronger vasorelaxation than the original extract and they had a higher phenolic content. Conclusions: Parkia biglobosa leaf extract is able to induce endothelium-dependent NO- and EDHFmediated relaxation in porcine coronary artery rings. The vasorelaxant activity is dependent on their phenolic content and appears to involve mainly procyanidins.
Keywords: Parkia biglobosa (Mimosaceae); Polyphenols; Procyanidins; Vasorelaxant; Coronary artery; Endothelium